Thematic television and child: Television viewing habits of primary school students - Do?an, Adem; Göker, Göksel (My University, 2012)
Children comes at the beginning of part that most affected from television, even been dependent, in nowadays society. Children who is on stage of growing up of detection level and ability to interpret, exposure to effects of understanding of television broadcasting, especially with starting of the publication thematic television channels. In this study, with case of Elazi?, examined on that positive or negative effects of television on children, understanding of publishing of thematic child television channels, viewpoint of primary school student to thematic child channel, expectations of primary school student from family child channels and effects of child channel on children. According to findings from research have been identified that the majority of the sample group watching television an average of 1 to 2 hours per day, most prefer to watch cartoons and children's program, in addition to serial films for adults watching by the children and broadcasting contain violence reach the children.
Tematik televizyon ve çocuk: Ilkö?retim ö?rencilerinin televizyon izleme alişkanliklari
Keywords: Child; Effects of television; Television; Thematic child channels